Implementasi Model Pentahelix dalam Pengembangan Pariwisata di Kota Banjarmasin - Fitria Mumtazah; Muhammad Noor; Mayogi Araffi (Universitas Persada Indonesia YAI, 2025)
Currently, tourism is considered an important contributor to economic growth. The unique natural conditions of the city of Banjarmasin will certainly create benefits for this region, especially in the tourism industry. However, in the last five years, the number of tourists in the city of Banjarmasin has continued to decline. This study aims to determine the role of academics, businesses, communities, government, and the media in the development of tourism in the city of Banjarmasin. This study is descriptive and qualitative in nature. This research uses a literature study. The results show that academics in Banjarmasin City have contributed their thoughts, ideas, and best practices in research. Businesses have innovated and created new designs and infrastructure to increase the appeal of tourist attractions at each culinary location. The people of Banjarmasin have participated in developing tourism in terms of ideas, energy, funds, goods, expertise, and services. The government has issued a plan for developing tourism in Banjarmasin through the Regional Innovation System Roadmap, and has launched the Kriya sector. It has also redesigned the master plan so that the development of tourism in Banjarmasin has clear plans and targets. The government, community, and business actors have also utilized media as a means of promotion in developing tourism in Banjarmasin City, namely through websites, Instagram, Facebook, Twitter, WhatsApp, TikTok, or by showing videos during online activities such as seminars/webinars and others, as well as distributing brochures related to tourism in Banjarmasin City to 4-star and 5-star hotels.